Examination of Self-efficacy Beliefs of on performance (An empirical study on National level Players of team sports in Sri Lanka) - HPN, Perera; M, Jusoh; SMF, Azam; SRSN, Sudasinghe (International Journal of Scientific Research and Management (IJSRM), 2019)
The main goal of this study was identify the impact of Self-Efficacy on the performance of team sports players in Sri Lanka. Mainly it was focused to measure self-efficacy belief of team players and the experimental variable of the study was perceived performance. The study utilized a likert scale questionnaire which had been adopted from literature to obtain data for the study. The research model was tested using 308 subjects comprised of national level team players. Data were analyzed using SPSS and structural equation modeling with AMOS. Self-efficacy has proven to have a noticeable impact on subjective performance of the players. The recommendations included the strategies which can be utilized to enhance the self-efficacy belief of the players.